Integrasi Rain Garden pada Badan Jalan Kota Baru Parahyangan Bandung Barat - Rannu, Musa; Pratiwi, A. Andini Radisya; Juliar, Eka; Oktariana, Mochamad Qodir; Dzulfiyanto, Rian; Wildan, Aditya; Firdaus, Firdaus; Nugraha, Prina; Sumpeno, Yadi; Siregar, Chandra Afriade (TECHNO-SOCIO EKONOMIKA, 2025)
Rapid urbanization has led to an increased demand for land, often at the expense of the environment. In response, rain gardens have emerged as a popular and sustainable solution for managing stormwater. This study focuses on evaluating how rain gardens in Kota Baru Parahyangan (KBP), Bandung, contribute to improving community satisfaction and enhancing environmental quality.Using a descriptive qualitative approach, the research gathered data through in-depth interviews, observations, and documentation. The findings reveal that rain gardens in KBP effectively manage stormwater runoff, reduce flood risks, and improve air quality. Beyond these benefits, they also enhance biodiversity, beautify the surroundings, and support efforts toward achieving carbon neutrality, the environmental impact assessment (AMDAL) data for the KBP area indicates a reduction of 1°C in the local temperature. The community has expressed high satisfaction with the presence of rain gardens, recognizing their significant environmental benefits and positive impact on quality of life. However, the study also highlights challenges, such as the need for more regular maintenance. Overall, the adoption of rain gardens in KBP is a significant step toward building a sustainable urban environment. Integrating rain gardens into urban planning is strongly recommended to improve the quality of life in cities. The study also suggests expanding this initiative to other areas and emphasizes the importance of involving the community in planning and managing rain gardens to ensure their long-term success.